Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Problem Based Learning (PBL) Untuk Meningkatkan Motivasi Belajar Siswa - Aihsyatun Sholihah Sholihah (Cocos Bio, 2025)
Abstract:This study aims to: (1) Develop Student Worksheets (LKPD) based on Problem Based Learning (PBL) to increase student learning motivation. (2) To determine the feasibility of Student Worksheets (LKPD) based on Problem Based Learning (PBL). (3) To determine the effectiveness of Student Worksheets (LKPD) based on Problem Based Learning (PBL). This development research uses the Bord and Gall model which is carried out with 5 development stages, namely: preliminary research/pre-survey, planning, development of models/initial products, initial product trials, revision of initial product trials. The trial subjects in this study were material experts I, material experts II (Biology Teachers) and design experts, 30 field trial students at MA Darussolihin NW Kalijaga. Data collection techniques were carried out using questionnaires and data analysis using quantitative descriptive analysis techniques. Based on the results of data analysis and discussion, it can be concluded that the Student Worksheet (LKPD) product based on Problem Based Learning (PBL) to increase student learning motivation is feasible, valid, and effective for use during the learning process. The feasibility of the Student Worksheet (LKPD) can be seen from the average feasibility score from Subject Matter Expert I (81.00%), Subject Matter Expert II (Biology Teacher) (85.00%), Design Expert (91.67%), and Student Response (81.17%). This score qualifies as highly feasible. Furthermore, the effectiveness of the Problem-Based Learning (PBL)-based Student Worksheet (LKPD) can be seen from the average N-Gain obtained in the main field test of 0.53. Based on the average N-Gain obtained, it qualifies as moderate with a fairly effective level of effectiveness. The main field test showed an increase in student learning motivation of 22.83%. Keywords: Student Worksheet (LKPD), Problem-Based Learning (PBL), Learning Motivation.